The Role of Islamic Education in Installing National Values: Peran Pendidikan Islam dalam Penanamkan Nilai-Nilai Kebangsaan - Hilmi, Fuad; Maryana, Ina (Edukasi: Journal of Educational Research, 2025)
This study aims to discuss the role of Islamic education in instilling national values. Amidst the challenges of globalization and rapid social change, national identity is often under pressure. Islamic education has a strategic role in instilling national values ​​such as love of the homeland, tolerance, justice, and social solidarity to the younger generation. The research method used is qualitative descriptive with research subjects selected by purposive sampling. Data collection techniques include observation, interviews, and documentation. The research subjects include religious teachers, religious activity instructors, Islamic organization administrators, and students. The results of the study indicate that Islamic education plays an important role in shaping national awareness in the younger generation. Islamic values ​​that emphasize unity, peace, and justice are in line with the spirit of nationalism carried by the Indonesian nation. Data from observations, interviews, and documentation show that students who are active in religious activities and Islamic learning have a stronger sense of nationalism. The conclusion of this study confirms that a holistic Islamic education approach is very effective in instilling national values. Through the integration of spiritual, moral, and social values ​​in the education process, it is hoped that the younger generation will not only have strong faith but also a high sense of nationalism.